SCIENCE IN HADITH: PHILOSOPHICAL-HISTORICAL PERSPECTIVE - Siregar, Desi Fitriani (Journal of Islamicate Studies, 2019)
Since the beginning of its birth, Islam has given such great appreciation to science. In addition to the verses of the Qur'Än that position knowledge and knowledge people are very special, the Qur'an also encourages Muslims to pray for added knowledge, and say, my Lord, add to me knowledge of knowledge. In this connection the concept of reading, as one vehicle to increase knowledge, becomes very important, and Islam has from the beginning stressed the importance of reading. Searching for and studying is an obligation for both Muslim men and women. The Prophet pbuh, made the activity of seeking knowledge and knowledge needed by Muslims to enforce the affairs of their religion, as a duty that Fará¸ â€˜Ayn for every Muslim. The knowledge of Fará¸ â€˜Ayn is the knowledge that every person who is â€˜aqÄ«l balÄ«gh must practice it which includes; the science of â€˜aqÄ«dah, do the commands of Allah, and leave His prohibitions. One of the enlightenments brought by Islam to humanity is scientific thought that refers to the Qur'Än and á¸¤adÄ«th. Awareness of Muslim scientists who originate from the Qur'Än and á¸¤adÄ«th triggers the greatest achievements in science.